The Influence of Profitability and Leverage on Tax Avoidance with Transfer Pricing as a Moderating Variable (Mining Sector Companies Listed on IDX 2019-2023) - Puspitasari, Dana; Munari, Munari (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2024)
The study aims to examine and analyze the influence of profitability and leverage on tax avoidance with transfer pricing as a moderating variable. The research uses a quantitative approach. The population in this study includes all mining sector companies listed on the Indonesia Stock Exchange (IDX) for the years 2019-2023. The sample was selected using purposive sampling method, and based on predetermined criteria, a sample of 20 companies was obtained. The data used is secondary data obtained from the financial statements of the sampled companies. Data was analyzed using the Partial Least Square (PLS) technique. The results of this study indicate that profitability has a significant positive effect on tax avoidance, leverage has a negative and insignificant effect on tax avoidance, transfer pricing is unable to moderate the effect of profitability on tax avoidance, whereas transfer pricing can strengthen the negative effect of leverage on tax avoidance.